House dust mite allergy – Management - P. C. Kathuria; Manisha Rai (Indian Journal of Allergy Asthma and Immunology)
Allergen vulnerability is highly individual specific. House dust mites (HDMs) are major sources of airborne allergens, found not only in houses but also detected in workplaces and most schools. The two most common HDM species from the Pyroglyphidae family, namely Dermatophagoides pteronyssinus and Dermatophagoides farinae are responsible for 90% of sensitization and allergic symptoms. Clinical conditions due to HDM allergen are rhinitis, conjunctivitis, asthma and/or atopic dermatitis (AD), and rare severe systemic reaction. Accurate diagnosis by skin prick test, specific immunoglobulin E (extract and component-based), or nasal provocation test with standardized HDM extract in contest with clinically relevant exposure to dust mites is fundamental for successful treatment. Allergen immunotherapy (AIT) is the only treatment providing sustained efficacy for moderate-to-severe allergic rhinitis, allergic asthma, and AD. This review will mainly focus on the description of HDM allergens, immunology, efficacy, and HDM-AIT (subcutaneous immunotherapy and sublingual immunotherapy).